Impulsive Buying, Apa dan Kemana? Systematic Literature Review Mengenai Perkembangan Penelitian Impulsive buying pada 10 Tahun Terakhir - Ilham Medal Junjunan (LPPM UNIBI, 2022)
Impulsive buying is a topic that is deeply embedded in consumer behavior, both globally and in Indonesia itself. The topic of impulsive buying has been discussed for more than half a century. This article aims to find out the development of research on Impulsive buying in the last ten years, especially in the digital and social media era. This research is a Systematic Literature Review Research with a literature collection process assisted by the Harzing's Publish or Perish application. The results of this Systematic Literature Review found that research on impulsive buying has not had much meaningful updates in the last ten years, generally still focusing on physical products, not much has been researched on service products and experiences. Apart from that, the digital field is still very limited to E-Commerce in general. For Indonesia itself, it may be necessary to carry out a specific analysis on certain very unique E-commerce such as GoFood, or other service products that are digital but non-E-Commerce. The products studied were also dominated by hedonic products such as fashion, make-up and others. Not many have researched products that are actually utilitarian in nature but can lead to impulsive buying, such as baby equipment, exam equipment, or other things that are purchased for utilitarian purposes but on an impulse basis.